Solutions To Problems Arising In Agriculture In Uzbekistan In The Context Of The Digital Economy - Erkin, Shavqiev; Farkhod Fakhriddinovich, Ulugmurodov; Avazbek Sadullaevich, Karshiev; Ziyodulla, Rashidov (Research Parks Publishers, 2025)
This article explores challenges faced by Uzbekistan's agricultural sector in the context of the growing digital economy and proposes innovative solutions. It examines both macro-level issues, such as outdated infrastructure, inefficient resource management, and limited access to technology, and micro-level problems, including farm-level productivity, insufficient data-driven decision-making, and inadequate farmer education. The study emphasizes the role of digital tools, such as precision agriculture, IoT-based monitoring systems, and blockchain for supply chain transparency, in addressing these challenges. Additionally, it highlights the necessity of government policies, private sector collaboration, and capacity-building initiatives to accelerate the adoption of digital technologies in agriculture. By leveraging digital advancements, Uzbekistan can achieve sustainable agricultural growth and contribute to national food security and economic development.